2017
DOI: 10.1007/s11596-017-1806-9
|View full text |Cite
|
Sign up to set email alerts
|

Does hospital ownership influence hand hygiene compliance?

Abstract: The issue as to whether hospital ownership has an impact on the quality of care has long been a serious concern. Hand hygiene (HH) compliance is regarded as an important indicator of the quality of care in the control of hospital-acquired infections. However, little information is available on whether hospital ownership influences HH compliance. In this study, of 229 hospitals selected from Hubei province in China, 152 were public and 77 were private hospitals. A total of 23 652 healthcare workers (HCWs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…15,[23][24][25] High workload and facility ownership are additional factors linked with low compliances of hand hygiene as reported by studies in India and China, where low compliance of hand hygiene was noted more frequently in public compared to private facilities. [26][27][28] Although an improvement in hand hygiene compliance was observed in the current study, little improvement was observed in washing hands with water or ABHR for at least 2 minutes and wearing sterile gloves correctly before procedure. The main reason given was absence of previous training, in congruence with results reported by other studies.…”
Section: Discussioncontrasting
confidence: 46%
“…15,[23][24][25] High workload and facility ownership are additional factors linked with low compliances of hand hygiene as reported by studies in India and China, where low compliance of hand hygiene was noted more frequently in public compared to private facilities. [26][27][28] Although an improvement in hand hygiene compliance was observed in the current study, little improvement was observed in washing hands with water or ABHR for at least 2 minutes and wearing sterile gloves correctly before procedure. The main reason given was absence of previous training, in congruence with results reported by other studies.…”
Section: Discussioncontrasting
confidence: 46%
“…Our finding that compliance to hand hygiene is influenced by facility ownership: better in private than public, has also been reported by a recent study conducted in China. It reported compliance in 77 private and 152 public hospitals with compliance to be significantly better in private than public (79, 67%, p < 0.05) [20].…”
Section: Discussionmentioning
confidence: 97%
“…In a 2016 study from Rajasthan where primary health care facilities were also included, the hand hygiene compliance during childbirth was 2% in 240 observed cases at baseline [25] which is very low in comparison to our study (34%) that included only secondary and tertiary level facilities. Poor hand hygiene adherence has long been a concern not only in low [17,20,21,25] but also in high resource settings across the globe [8,26] . Hand hygiene compliance is reported as ranging from 8 to 39% in Sub-Saharan African countries [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations